'Not my government!' The role of norms and populist attitudes on voter preferences for government formation after the election. (January 2021) - Plescia, Carolina; Eberl, Jakob-Moritz
Processes of coalition government formation have recently become subject to increasing delay across Europe. There also appears to be a concurrent surge in the success of 'populist' challengers, who tend to reject key features intrinsic to pluralism such as elite bargaining and compromise. Against this background, this article investigates for the first time citizen preferences for which party should get the mandate to form the government and which parties should definitely be excluded from government formation. We focus specifically on the effect that political knowledge and populist attitudes have on citizen preferences for government formation. We find that both political knowledge and populist attitudes are essential in explaining voters' willingness or unwillingness to accept the fundamental prerequisite of coalition bargaining and political compromise. These findings have important implications for our understanding of citizens' attitudes and political representation.